Profiles, potential and string tension of the flux tube in SU(2) and SU(3) lattice gauge theories - Chagdaa, Sodbileg; Galsandorj, Enkhtuya; Purev, Battogtokh (Proceedings of the Mongolian Academy of Sciences, 2020)
In this work, we have studied SU(2) and SU(3) gauge theories explaining the colour interaction of a quark and an antiquark, and their identical and dissimilar properties. Using both gauge theories, we have performed simulations under similar conditions and have studied the differences in the results obtained. We have compared the transverse and longitudinal profiles of the chromoelectric and chromomagnetic components of the field strength, potential, and temperature-dependent string tension of the flux tube. The potential between the quark and antiquark of the SU(3) theory was larger than that of the SU(2) under all temperatures. The string tension of SU(3) tends to stabilize starting from the critical temperature while that of SU(2) has a gradual decreasing feature.